Utilization Study of Void Mine For Sustainable Environment of The Limestone Mining Sector at PT Semen Baturaja (Persero) Tbk - Hisni Rahmi; Didik Susetyo; Restu Juniah (Research Centre of Inorganic Materials and Complexs, 2019)
Event open-pit mining methods in the exploitation of limestone by PT Semen Baturaja (Persero) Tbk cause depletion of water, air, and soil. At the end of mining activities will leave ex-mine land in the form of void and non void (empty land). Reclamation and Postmining must be carried out by the company according to the mandate of Government Regulation No. 78 year 2010. Reclamation and post-harvest activities on ex-non void mines can be revegetation activities, while void can be used as reservoirs for raw water sources. The aim is to maintain the sustainability of natural resources and water in the limestone mining environment. The research aims to determine the condition of void water produced from limestone mining activities for a sustainable environment. The method used in this study is using the pollution index method. The results showed that the water in the sump inlet and quarry outlet experienced mild pollution. Pollution index at the location of the limestone mine sump inlet worth 2.14 and for oulet quarry worth 2.07. This shows that mine void water is not feasible to be used as raw water, so water treatment needs to be done so that it meets the established quality standards. If void water comply the prescribed quality standards, environmental sustainability in the limestone mining sector can be achieved during during the life of the mine, post mining, until after the post-mining period.